Hydrolysis of crambe oil by enzymatic catalysis: An evaluation of the operational conditions. Issue 6 (2nd November 2018) - Tavares, Fernanda; Silva, Edson A. Da; Pinzan, Fernanda; Canevesi, Rafael S.; Milinsk, Maria C.; Scheufele, Fabiano B.; Borba, Carlos E.
Abstract: In this work, the enzymatic hydrolysis of the crambe oil by using a commercial immobilized lipase Lipozyme RM IM was evaluated. The effect of the operational conditions, such as temperature, water/oil molar ratio, enzyme/substrate mass ratio and stirring speed were assessed based on the experimental designs. The experiments were performed in a closed and batch system with controlled temperature and stirring speed. In addition, the kinetics of the process was studied in the best operational conditions, wherein the experimental data were obtained and described by a mathematical model. The influence of the operational conditions was assessed based on the measured values of the free fatty acids (FFA) produced by the enzymatic hydrolysis. In 4 h of reaction, a yield of 42.6% was observed and the most significant operational conditions were the enzyme/substrate mass ratio and stirring speed. By the kinetic investigation, an initial reaction rate of 3.5 × 10 4 mol mL −1 h −1 and a maximum yield of 74% were observed after 40 h of reaction (in the equilibrium condition). The mathematical model was not only able to adequately describe the experimental data of FFA concentrations profiles but also showed predictive capacity to independents assays in different operational conditions. Therefore, based on the simulation analysis of the enzymatic hydrolysis of the crambe oil, the model can be useful for process optimization and phenomenological studies.